Comorbidity profile and outcomes in patients with chronic heart failure in a Latin American country: Insights from the Colombian heart failure registry (RECOLFACA). (1st May 2023) - Campbell-Quintero, Sebastián; Echeverría, Luis Eduardo; Gómez-Mesa, Juan Esteban; Rivera-Toquica, Alex; Rentería-Asprilla, Carlos Alberto; López-Garzón, Nelson Adolfo; Alcalá-Hernández, Armando Enrique; Accini-Mendoza, José Luis; Baquero-Lozano, Gary Andrés; Martínez-Carvajal, Argemiro Ramon; Cadena, Alberto; Zarama-Márquez, Mario Hernán; et al.
Abstract: Background: Heart failure (HF) is usually accompanied by cardiovascular and non-cardiovascular comorbidities, which may significantly impact its prognosis. In this study we aimed to characterize the comorbidity profile and its impact in mortality in patients with HF diagnosis from the Colombian Heart Failure Registry (RECOLFACA). Methods: RECOLFACA enrolled adult patients with HF diagnosis from 60 centers in Colombia during the period 2017–2019. The primary outcome was all-cause mortality. A Cox proportional hazards regression model was used to assess the impact of the comorbidities in mortality. A p -value of <0.05 was considered significant. Results: From the total 2528 patients included in the registry, 2514 patients (58% males, mean age 68 years) had information regarding comorbidity diagnoses. 2321 patients (92.3%) reported at least one comorbidity. Arterial hypertension was the most frequent individual diagnosis (72%; n = 1811), followed by anemia (30.1%, n = 726). The most frequently observed coexisting comorbidities were coronary disease (CHD) with dyslipidemia, and chronic kidney disease (CKD) with type 2 Diabetes Mellitus (T2DM). Different patterns of comorbidity coexistence were observed when comparing HF patients by sex and left-ventricular ejection fraction (LVEF) classification. The only comorbidities that were significantly associated with mortality after multivariate adjustment were T2DM (HR 1.45. 95% CI 1.01–2.12), anemia (HR 1.48. 95% CI 1.02–2.16), and CHD (HR 1.59. 95% CI 1.09–2.33). Conclusion: Multiple comorbidities were frequently observed in the patients from the RECOLFACA. T2DM, anemia and CHD were significantly associated with a higher risk of mortality, highlighting the importance of promoting an optimal follow-up and control of these conditions. Highlights: >90% of the patients had at least one comorbidity. Hypertension, anemia, and CHD were the most frequent comorbidities. T2DM, anemia and CHD were significantly associated with a higher risk of mortality.